A recombinant subunit vaccine candidate produced in plants elicits neutralizing antibodies against SARS-CoV-2 variants in macaques - Khorattanakulchai, Narach; Srisutthisamphan, Kanjana; Shanmugaraj, Balamurugan; Manopwisedjaroen, Suwimon; Rattanapisit, Kaewta; Panapitakkul, Chalisa; Kemthong, Taratorn; Suttisan, Nutchanat; Malaivijitnond, Suchinda; Thitithanyanont, Arunee; Jongkaewwattana, Anan; Phoolcharoen, Waranyoo (Frontiers in Plant Science, 2022)
Since the outbreak of the coronavirus disease (COVID) pandemic in 2019, the development of effective vaccines to combat the infection has been accelerated. With the recent emergence of highly transmissible severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOC), there are concerns regarding the immune escape from vaccine-induced immunity. Hence an effective vaccine against VOC with a potent immune response is required. Our previous study confirmed that the two doses of the plant-produced receptor-binding domain (RBD) of SARS-CoV-2 fused with the Fc region of human IgG1, namely Baiya SARS-CoV-2 Vax 1, showed high immunogenicity in mice and monkeys. Here, we aimed to evaluate the immunogenicity of a three-dose intramuscular injection of Baiya SARS-CoV-2 Vax 1 on days 0, 21, and 133 in cynomolgus monkeys. At 14 days after immunization, blood samples were collected to determine RBD-specific antibody titer, neutralizing antibody, and pseudovirus neutralizing antibody titers. Immunized monkeys developed significantly high levels of antigen-specific antibodies against SARS-CoV-2 compared to the control group. Interestingly, the sera collected from immunized monkeys also showed a neutralizing antibody response against the SARS-CoV-2 VOCs; Alpha, Beta, Gamma, Delta, and Omicron. These findings demonstrate that a three-dose regimen of Baiya SARS-CoV-2 Vax 1 vaccine elicits neutralizing immune response against SARS-CoV-2 variants.